(untitled) (International Journal of Environmental Sciences, 2025)
This study investigates the impact of Corporate Social Responsibility (CSR) on passenger loyalty in the Indian civil aviation industry, emphasizing the mediating roles of passenger satisfaction, brand trust, and airline image. Drawing on data from 335 respondents across India and analyzed using Structural Equation Modeling (SEM), the findings reveal that CSR significantly influences satisfaction, trust, and image, which in turn enhance loyalty. However, the direct effect of CSR on loyalty was not statistically significant, highlighting the importance of perceptual and emotional mediators in shaping customer behavior. The results underscore that CSR alone does not drive loyalty unless integrated with positive customer experiences and strong brand perceptions. The study offers a robust conceptual framework for airline stakeholders to align CSR initiatives with service quality and brand engagement strategies. These insights are critical for positioning CSR not just as a compliance requirement but as a strategic tool for customer retention and competitive advantage.